LITERATURE STUDY ON THE POTENTIAL OF EXOSOMES FROM MESENCHYMAL STEM CELLS FOR BONE REGENERATIVE THERAPY - Emmanuela, Natasya
Severe bone damage from disease or an accident can cause chronic pain to permanent disability. The use of exosomes is now being widely studied for cell-free therapy in the treatment of bone diseases because of the cargo they contain and their safety compared to stem cell-based therapies. In this literature study, the potential of exosome’s cargo from mesenchymal stem cells and their delivery methods to heal bone disease has been investigated. The study was conducted using Google Scholar with certain keywords, Scimagojr.com and Mendeley Desktop and obtained 79 articles from 2015 to 2022. The literature search results showed the ability of exosomes to promote osteogenesis, angiogenesis, and inhibit apoptosis in various bone defects. This potential is related to the cargo in exosomes, in particular miRNAs that can target specific genes and signaling pathways specifically, related to bone regeneration. The diversity of miRNA functions in exosomes can be influenced by various factors, such as tissue age, as well as the type and timing of differentiation of mesenchymal stem cells. In the application of exosomes for bone treatment, the delivery method is also of great concern. The method used can be in the form of injection, the use of a scaffold with exosome immobilization that can be implanted directly or injected (injectable scaffold) in the area of bone damage. The injection method tends to be less effective, while the scaffold implant method is less practical to deliver exosomes. Based on the results of the literature study, it can be concluded that exosomes derived from mesenchymal stem cells contain miRNAs, one of which is miR-21 which can promote bone regeneration, so it has the potential to be used in bone regenerative medicine. The most effective exosome delivery method is by using scaffold, particularly injectable scaffold because it is able to release exosomes in a longer period of time, and can fill irregular-shaped bone damage.